Estudo da viabilidade do desenvolvimento de uma formulação a base de extratos de Malva sylvestris e Arctium lappa para atividade antiacne - Cubas, Verônica Marin (2021)
Acne is a chronic skin inflammation that affects young people and adults of different age groups. Its etiology is multifactorial and triggers from mild injuries to comedogenic injuries that can cause scars that are sometimes unsightly. Several drugs have been used to treat acne, however, conventional therapies have, for the most part, enough side effects to limit treatments to affected patients. Among traditional treatments, the use of antibiotic therapies is prevalent, triggering Cutibacterium acnes resistance to these agents. Based on the above, there is an interest in developing new treatments for acne, including alternative complementary medicine (CAM). CAM uses, among other therapies, those that employ herbal medicines, considering the presence of potentially effective compounds, which have already shown anti-inflammatory and antibacterial effects in this condition. The increased demand in the population's demand for treatments that use herbal medicines in their composition leveraged the cosmetic industry's investments in treatments with these attributes. Thus, exploring the use of herbal medicines that have potential for their use for alternative treatments is necessary and should be deepened. This study aimed to develop a formulation based on the herbal medicines Malva sylvestris L. and Arctium lappa L. with anti-acne purpose. For this purpose, pharmaceutical formulas for topical use (serum) previously elaborated containing individual and associated extracts were submitted to the tests. In the accelerated stability test, the formulations were subjected to different conditions of temperature and times, which were later evaluated on organoleptic and chemical physical characteristics such as pH and density. For the investigation of the antibacterial capacity of herbal extracts of M. sylvestris and A. lappa, formulations containing the extracts in an associated and isolated form at concentrations of 0.25; 0.50; 0.75; 1.00; 5.00; 10.00, 25.00 and 50.00 (g/L) were submitted to the disk and diffusion test and the minimum inhibitory concentration (MIC). In both tests the evaluation was carried out in aerobiosis and microaerophilia. The results of the accelerated stability test showed that the formulas containing the extracts remained stable at room temperature and exposed to sunlight, considering the parameters evaluated during the time that the test lasted. In the CIM tests and in the disk and diffusion test, the extracts used in this study did not show the capacity to inhibit the growth of the bacteria that were submitted to the test (Cutibacterium acnes, Staphylococcus aureus and Staphylococcus epidermidis). With the research carried out in scientific articles about medicinal plants to support this study, it was possible to develop and publish the article “Alternative medicine based on medicinal plants in the treatment of acne” in the journal Research, Development and Society.